RBFOX2/GOLIM4 Splicing Axis Activates Vesicular Transport Pathway to Promote Nasopharyngeal Carcinogenesis. Issue 16 (28th June 2021) - Luo, Chun‐Ling; Xu, Xiao‐Chen; Liu, Chu‐Jun; He, Shuai; Chen, Jie‐Rong; Feng, Yan‐Chun; Liu, Shu‐Qiang; Peng, Wan; Zhou, Ya‐Qing; Liu, Yu‐Xiang; Wei, Pan‐Pan; Li, Bo; et al.
Abstract: 20–30% of patients with nasopharyngeal carcinoma (NPC) develop distant metastasis or recurrence leading to poor survival, of which the underlying key molecular events have yet to be addressed. Here alternative splicing events in 85 NPC samples are profiled using transcriptome analysis and it is revealed that the long isoform of GOLIM4 (‐L) with exon‐7 is highly expressed in NPC and associated with poor prognosis. Lines of evidence demonstrate the pro‐tumorigenic function of GOLIM4‐L in NPC cells. It is further revealed that RBFOX2 binds to a GGAA motif in exon‐7 and promotes its inclusion forming GOLIM4‐L . RBFOX2 knockdown suppresses the tumorigenesis of NPC cells, phenocopying GOLIM4‐L knockdown, which is significantly rescued by GOLIM4‐L overexpression. High expression of RBFOX2 is correlated with the exon‐7 inclusion of GOLIM4 in NPC biopsies and associated with worse prognosis. It is observed that RBFOX2 and GOLIM4 can influence vesicle‐mediated transport through maintaining the organization of Golgi apparatus. Finally, it is revealed that RAB26 interacts with GOLIM4 and mediates its tumorigenic potentials in NPC cells. Taken together, the findings provide insights into how alternative splicing contributes to NPC development, by highlighting a functional link between GOLIM4‐L and its splicing regulator RBFOX2 activating vesicle‐mediated transport involving RAB26. Abstract : Alternative splicing events are profiled in nasopharyngeal carcinoma (NPC) using transcriptome analysis, and a high expression of the long isoform of GOLIM4 containing exon‐7 (GOLIM4‐L) to be associated with poor survival of NPC is identified. A functional link between GOLIM4‐L and its splicing regulator RBFOX2 is also revealed, which activates vesicle‐mediated transport through maintaining Golgi complex integrity involving RAB26.